Developing Nepal's medicines pricing policy: evidence synthesis and stakeholders' consultation - Zaheer-; Santosh Dulal; Narayan Prasad Dhakal; Madan Kumar Upadhyaya; Birna Trap (Taylor & Francis Group, 2024)
ABSTRACTObjectives The objectives of this paper are to (a) explore stakeholders' opinions regarding Nepal's existing medicines pricing practices/situation and (b) build and present a set of medicines pricing policies for Nepal.Methods A review of the literature and field visits to community retail pharmacies, hospital pharmacies, wholesalers, and distributor outlets in Kathmandu were conducted to assess the medicines pricing situation. Following the literature review, preliminary meetings with stakeholders and field visits were held and a draft interview guide was prepared. Consultative sessions subsequently were undertaken in Kathmandu, Nepal, in January 2023 with representatives from the Department of Drug Administration, Ministry of Health and Population, Association of Pharmaceutical Producers of Nepal, consumer groups, Transparency International, Medicines Importers Association of Nepal/ Pharmaceutical Distributors Association of Nepal, Nepal Chemist and Druggist Association, and Nepal Pharmaceutical Association. Notes were taken during these meetings regarding issues and concerns raised as well as experiences and recommendations for the future, as outlined in the interview guide.Results The stakeholders in general stated that they do not have any objection to price regulation; however, they believe such regulation should be subject to periodic review. Both the importers and the Ministry of Health and Population have the view that an independent body/authority should be charged with regulating the prices of medicines. A set of policy options to be considered for use in Nepal include cost-plus pricing, external price referencing, internal reference pricing, and mark-up regulations.Conclusion Key issues related to pricing were identified and suggest that a set of pricing policies and updated regulations need to be considered to establish changes that are transparent, rational, and acceptable to the related stakeholders. Hence, suggestions made in this paper could be useful to inform a rational and fair pricing structure and to improve access to medicines.